William S. Burroughs Cutting Up the Century - Wermer-Colan, Alex; Hawkins, Joan, 1953- (Book collections on Project MUSE., 2019)
William S. Burroughs Cutting Up the Century is the definitive book on Burroughs' overarching cut-up project and its relevance to the American twentieth century. Burroughs's Nova Trilogy (The Soft Machine, Nova Express, and The Ticket That Exploded) remains the best-known of his textual cut-up creations, but he committed more than a decade of his life to searching out multimedia for use in works of collage. By cutting up, folding in, and splicing together newspapers, magazines, letters, book reviews, classical literature, audio recordings, photographs, and films, Burroughs created an eclectic and wide-ranging countercultural archive. This collection includes previously unpublished work by Burroughs such as cut-ups of work written by his son, cut-ups of critical responses to his own work, collages on the Vietnam War and the Watergate scandal, excerpts from his dream journals, and some of the few diary entries that Burroughs wrote about his wife, Joan. William S. Burroughs Cutting Up the Century also features original essays, interviews, and discussions by established Burroughs scholars, respected artists, and people who encountered Burroughs. The essays consider Burroughs from a range of starting points--literary studies, media studies, popular culture, gender studies, post-colonialism, history, and geography. Ultimately, the collection situates Burroughs as a central artist and thinker of his time and considers his insights on political and social problems that have become even more dire in ours.